Juan Ginés de Sepúlveda’s Democrates secundus, rhetoric or ideology? - Urbano, Francisco Castilla (Pensamiento. Revista de Investigación e Información Filosófica, 2014)
Democrates secundus can be considered as Juan Ginés de Sepúlveda’s most polemical and cited text. This book was not published during the author’s whole life, a fact that has been justified on ideological, moral, political and even guild grounds. This article places the book in the ideological context of civic humanism, assimilated by Sepúlveda during his Italian stage. This humanism takes Rome and its classics as a model where the values of virtue, glory, culture, military bravery and patriotism are used to establish the Spanish superiority over the Indians. The just war would be the instrument applied to make real that superiority.